Addition of chemotherapy to nivolumab after PD-1 inhibitor failure as bridge to allogeneic stem cell transplantation in classical Hodgkin's lymphoma: report on three cases and literature review. (August 2021) - Romero, Samuel; Balaguer-Roselló, Aitana; Montoro, Juan; Beneit, Paola; Martínez, Amelia; Ruiz, Cristina; Andreu, Rafael; Guerreiro, Manuel; Arnao, Mario; Montava, Alberto; Vicente, Ana I.; Jarque, Isidro; et al.
The poor prognosis of refractory or relapsed (R/R) classical Hodgkin's lymphoma (cHL) after autologous stem cell transplantation has improved greatly due to the introduction of brentuximab vedotin and PD-1 inhibitors. However, the duration of response achieved with these novel agents is too short. The information about the management of patients after anti-PD-1 therapy failure is very limited in cHL, although chemotherapy alone or combined with PD-1 inhibitors has shown encouraging results. We report three cases of heavily pretreated cHL, refractory to nivolumab monotherapy, successfully rescued with the addition of chemotherapy to nivolumab, as a bridge to allogeneic stem cell transplantation (allo-SCT). All three patients presented poor clinical features such as three to four previous lines including brentuximab vedotin and autologous stem cell transplantation, refractoriness to the last line of therapy previous to nivolumab, and rapid disease progression. Notwithstanding these characteristics and nivolumab failure, they achieved a complete response after the addition of chemotherapy, were consolidated with allo-SCT, and still remain in complete response. There are few studies concerning the combination of PD-1 inhibitors and chemotherapy after nivolumab failure, including one retrospective study and one phase II trial with nivolumab plus bendamustine. Therefore, only few patients are consolidated with allo-SCT. However, there are several ongoing trials investigating new combinations of chemotherapy and PD-1 inhibitors in R/R cHL, as well as in first line. All these data suggest that anti-PD-1 therapy may reprogram the immune system, activating and inhibiting effector and immunosuppressive cells, respectively, leading to overtake of chemorefractoriness. Allo-SCT can increase the immune-related events of patients treated with anti-PD-1 previously, consistent on acute graft- versus -host disease, sinusoidal obstruction syndrome, and noninfectious febrile syndrome. In conclusion, the combination of PD-1 inhibitor and chemotherapy may be a feasible therapy after anti-PD-1 treatment failure as a bridge to allo-SCT.